Early evolution of radial glial cells in Bilateria. Issue 1859 (19th July 2017) - Helm, Conrad; Karl, Anett; Beckers, Patrick; Kaul-Strehlow, Sabrina; Ulbricht, Elke; Kourtesis, Ioannis; Kuhrt, Heidrun; Hausen, Harald; Bartolomaeus, Thomas; Reichenbach, Andreas; Bleidorn, Christoph
Abstract : Bilaterians usually possess a central nervous system, composed of neurons and supportive cells called glial cells. Whereas neuronal cells are highly comparable in all these animals, glial cells apparently differ, and in deuterostomes, radial glial cells are found. These particular secretory glial cells may represent the archetype of all (macro) glial cells and have not been reported from protostomes so far. This has caused controversial discussions of whether glial cells represent a homologous bilaterian characteristic or whether they (and thus, centralized nervous systems) evolved convergently in the two main clades of bilaterians. By using histology, transmission electron microscopy, immunolabelling and whole-mount in situ hybridization, we show here that protostomes also possess radial glia-like cells, which are very likely to be homologous to those of deuterostomes. Moreover, our antibody staining indicates that the secretory character of radial glial cells is maintained throughout their various evolutionary adaptations. This implies an early evolution of radial glial cells in the last common ancestor of Protostomia and Deuterostomia. Furthermore, it suggests that an intraepidermal nervous system—composed of sensory cells, neurons and radial glial cells—was probably the plesiomorphic condition in the bilaterian ancestor.